The mission of St. Augustine to England according to the original documents: being a handbook for the thirteenth centenary - Mason, Arthur James (The University Press, 1897)
Preface.--Chronological table.--Documents relating to the mission of St. Augustine and his companions.--The political outlook of Europe in 597. By C. W. Oman.--The mission of Augustine and his companions. By the editor.--The landing-place of St. Augustine. By T. McK. Hughes.--On some liturgical points relating to the mission of St. Augustine. By the Rev. H. A. Wilson.